Tattoo removal by non-professionals: medical and forensic considerations - Karsai, Syrus; Krieger, Gerd; Raulin, Christian (Journal of the European Academy of Dermatology and Venereology, 2010)
Tattoos are common phenomena in the western world and the demand for their removal has become widespread in the recent years. The introduction of quality-switched lasers has provided an effective removal method that is increasingly being exploited by tattoo studios themselves. Dermatologists, however, are frequently confronted with complications and side effects of tattoo removals that were performed by non-professionals. The objective of this study is to assess potential risks and pitfalls of laser tattoo removal when performed by medical laymen. The methods followed are systematic and evidence-based review of the literature. Four major problem areas were identified: rare but potentially severe allergic or toxic effects of decomposition products of the tattoo pigments; bodily harm caused by out-of-specification usage of the laser devices; malignant disease that is obscured within the area of a tattoo and requires meticulous dermatological diagnosis; and insufficient pre-operative consultation of patients about the risks, side effects and realistic expectations on the therapeutic outcome. We came to a conclusion that tattoo laser removal by medical laymen is unacceptable from the point of view of patient safety and the laws need to ban this practice swiftly.